2013
DOI: 10.1242/jeb.074153
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection and behaviour – location, location, location?

Abstract: SummaryParasite location has been proposed as an important factor in the behavioural changes observed in rodents infected with the protozoan Toxoplasma gondii. During the chronic stages of infection, encysted parasites are found in the brain but it remains unclear whether the parasite has tropism for specific brain regions. Parasite tissue cysts are found in all brain areas with some, but not all, prior studies reporting higher numbers located in the amygdala and frontal cortex. A stochastic process of parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 71 publications
3
156
0
5
Order By: Relevance
“…B 282: 20150042 tyrosine hydroxylase-like genes from T. gondii can result in subregion-specific changes in dopamine concentrations [43]. This is pertinent because T. gondii does not exhibit an exclusive tropism to nucleus accumbens or its sub-regions [44]. Toxoplasma gondii has earlier been reported to cause structural changes in neurons of host brain [45].…”
Section: Discussionmentioning
confidence: 99%
“…B 282: 20150042 tyrosine hydroxylase-like genes from T. gondii can result in subregion-specific changes in dopamine concentrations [43]. This is pertinent because T. gondii does not exhibit an exclusive tropism to nucleus accumbens or its sub-regions [44]. Toxoplasma gondii has earlier been reported to cause structural changes in neurons of host brain [45].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in cell cultures have demonstrated that dopamine increases the replication of T. gondii tachyzoites [118]. This biochemical mechanism may play a role in the behavioral changes observed, which would result from the involvement of catecholaminergic neurons and consequent dopaminergic hyperactivity [19].…”
Section: The Importance Of Dopamine and Other Neurotransmittersmentioning
confidence: 99%
“…Therefore, this parasite has genes that allow it to "manipulate" the behavior of the host and facilitate its capture by the cat, its definitive host, thereby favoring parasite survival. The presence of these genes is consequently an evolutionary advantage of T. gondii [19].…”
Section: Studies On Gene-infection Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of that, Toxoplasma directly synthesizes an enzyme that can increase the host's dopamine production even further (Gaskell, Smith, Pinney, Westhead, & McConkey, 2009). Indeed, in vitro, dopamine release has been found to be seven times larger in Toxoplasma--infected mouse cells than in uninfected ones; in vivo, the effect is estimated to be larger still (Prandovszky et al, 2011; for discussion of related evidence, see McConkey et al, 2013). Up--regulation of the dopamine system has been associated with both reckless sensation seeking (e.g., Norbury, Manohar, Rogers, & Husain, 2013) and positive schizophrenia symptoms (for a review, see Kantrowitz & Javitt, 2010).…”
Section: Mechanisms Of Toxoplasma's Integration In the Human Superorgmentioning
confidence: 99%